A COGNITIVE AND PRAGMATIC APPROACH TO METAPHOR IN ENGLISH AND UZBEK POLITICAL DISCOURSE - Ergasheva Ozodabonu Bahodirjon qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: Metaphor is a powerful linguistic and cognitive tool frequently employed in political discourse to influence public perception and construct ideological narratives. This article examines the use of metaphor in English and Uzbek political speeches from both cognitive and pragmatic perspectives. It explores how metaphors conceptualize political realities and how they are pragmatically used to persuade, legitimize authority, and frame complex social issues. Through comparative analysis, the study reveals cultural, contextual, and functional similarities and differences in metaphor usage across both languages.